Symbol in Short Story of Mahmood Jandari (College of Basic Education Research Journal, 2025)
Mahmood Jandari stands among  pioneers of short story writers locally, and nationally. He belongs to  sixties generation who brought about  turning point in  short story. He is one of the few names that worked on experimentation and modernity in  Iraqi narrative art, especially utilizing  symbols of history, myths, wonders, color, and  intersection of time, place, and characters in multiple forms. This research aimed to study  historical symbol in  short story of Mahmood Jandari.This research consists of an introduction and three sections. The introduction included defining  concept of  historical symbol. First section  devoted to  study  historical symbol in  story collection ( Years of Thirst), second    studies  historical symbol in his story collection (The Siege), while third section dealt with historical symbol in  his story collection ( Terraces of the gods).Research adopted an analytical method of  historical symbol in  short story of Mahmood Jandari, according to  objective analysis to demonstrate  aesthetic value of narrative texts.
Keywords: Learning together strategy; social interaction; special education students